Efektivitas Pembelajaran IPA Berbasis Project Based Learning dengan V-LABIO dalam Meningkatkan Pemahaman Konsep Siswa - Sri Indriyani; Berry Kurnia Vilmalla (PT. Nawa Edukasi Nusantara, 2026)
The rapid advancement of digital technology has encouraged the development of innovative learning approaches to improve the quality of science education. One promising approach is the integration of Project-Based Learning (PjBL) with Virtual Laboratory Biology (V-LABIO) to create a more interactive and student-centered learning environment. This study aims to examine the effectiveness of science learning based on PjBL integrated with V-LABIO in improving students' conceptual understanding. The study employed a descriptive qualitative literature review by analyzing 25 scientific articles, consisting of 15 accredited national journals and 10 reputable international journals published within the last ten years. The analysis involved identifying, comparing, and synthesizing research findings related to the implementation of PjBL and virtual laboratories in science education. The findings indicate that the integration of PjBL and V-LABIO consistently enhances students' conceptual understanding compared to conventional learning approaches. In addition, this integrated approach contributes to improving learning motivation, critical thinking, creativity, scientific literacy, science process skills, problem-solving abilities, and collaboration. Virtual laboratories also facilitate the visualization of abstract scientific concepts, making the learning process more interactive, flexible, and meaningful. Therefore, science learning based on Project-Based Learning supported by V-LABIO can serve as an effective instructional strategy to enhance students' conceptual understanding while fostering essential twenty-first-century competencies.